(untitled) (Journal of Pharma Insights and Research, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic, progressive metabolic dysregulation characterized by the dual defects of peripheral insulin resistance and pancreatic β-cell failure. The global escalation of T2DM correlates strongly with shifting lifestyle patterns, urbanization, and the obesity epidemic, posing a substantial challenge to healthcare systems. Pathophysiologically, the disease involves complex molecular disruptions, including impaired insulin signaling pathways, lipotoxicity, glucotoxicity, and systemic inflammation, which collectively compromise glucose homeostasis. Persistent hyperglycemia precipitates a wide spectrum of systemic sequelae, categorized into microvascular pathologies such as nephropathy, retinopathy, and neuropathy and macrovascular complications, including coronary artery disease and cerebrovascular accidents. Early diagnosis remains challenging due to the frequent asymptomatic clinical presentation, necessitating rigorous screening protocols using glycated hemoglobin and fasting plasma glucose metrics. Contemporary management paradigms have evolved beyond mere glycemic control to prioritize cardiorenal protection. Therapeutic strategies now integrate lifestyle modifications with a diverse pharmacopeia, ranging from foundational biguanides to novel sodium-glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists. This review explains the etiological mechanisms, epidemiological trends, diagnostic standards, and multifaceted therapeutic approaches essential for optimizing clinical outcomes and mitigating the long-term burden of the disease